2017
DOI: 10.1124/jpet.117.245126
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Influence of Pregnancy on Nicotine Metabolic Pathways

Abstract: Nicotine metabolism increases in pregnancy, which may contribute to the difficulties that pregnant women have in quitting smoking. We aimed to determine the extent and timing of changes in nicotine metabolic pathways, including C-oxidation, N-glucuronidation, and the pregnancy-induced influences on the activity of enzymes mediating these pathways (CYP2A6 and UGT2B10, respectively). Current smoking pregnant women ( = 47) provided a urine sample during early pregnancy (12.5 weeks), late pregnancy (28.9 weeks), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…In particular, MSE is the largest modifiable risk factor for the development of asthma. Although the harmful effect of smoking is well-known in the general public, smoking mothers find it difficult to quit due to nicotine addiction, even during pregnancy when nicotine metabolism is faster than non-pregnant status (Taghavi et al, 2018). A systematic review and meta-analysis in the Lancet showed that the top 3 countries with the highest smoking rate during pregnancy are Ireland (38.4%), Uruguay (29.7%), and Bulgaria (29.4%) (Lange et al, 2018).…”
Section: Epidemiology Of Asthmamentioning
confidence: 99%
“…In particular, MSE is the largest modifiable risk factor for the development of asthma. Although the harmful effect of smoking is well-known in the general public, smoking mothers find it difficult to quit due to nicotine addiction, even during pregnancy when nicotine metabolism is faster than non-pregnant status (Taghavi et al, 2018). A systematic review and meta-analysis in the Lancet showed that the top 3 countries with the highest smoking rate during pregnancy are Ireland (38.4%), Uruguay (29.7%), and Bulgaria (29.4%) (Lange et al, 2018).…”
Section: Epidemiology Of Asthmamentioning
confidence: 99%
“…Individuals who metabolize nicotine faster (who have higher CYP2A6 activity and NMR) smoke more to maintain similar levels of nicotine in the body compared to slower nicotine metabolizers (who have lower CYP2A6 activity and NMR) (22, 23, 25). The rate of nicotine metabolism is accelerated during pregnancy as evidenced by faster nicotine clearance (26) and a lower proportion of nicotine excreted unchanged (as a fraction of TNE) (27). Estrogen levels begin to rise after conception and are approximately five-fold and twenty-fold higher at early and late pregnancy, respectively, compared to pre-pregnancy levels (27).…”
Section: Introductionmentioning
confidence: 99%
“…The gestational age did not differ by group, which obviated controlling for this potential effect on NMR. 5 Most patients in the OAT group were being treated with methadone ( n = 27 or 79.4%; mean daily dosage = 91.0 mg [ SD = 62.6]) with the remainder receiving buprenorphine ( n = 7 or 20.6%; mean daily dosage = 14.3 mg [ SD = 3.2]). One participant reported a confirmed daily methadone dose of 360 mg; for the other 26 participants, the mean daily dose was 80.62 mg ( SD = 32.70).…”
Section: Resultsmentioning
confidence: 99%
“…Neither CPD nor PHQ-9 score was associated with NMR. Although changes in NMR have been observed across pregnancy, 5 we tested women at approximately the same gestational age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation